Linear groups with minimality condition for some infinite-dimensional subgroups - Dixon, M. R.; Evans, M. J.; Kurdachenko, L. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
Let F be a field, let A be a vector space over F, and let GL(F, A) be the group of all automorphisms of the space A. If H is a subgroup of GL(F, A), then we set aug _F (H) = _F (A(ωFH)), where ωFH is the augmentation ideal of the group ring FH. The number aug _F (H) is called the augmentation dimension of the subgroup H. In the present paper, we study locally solvable linear groups with minimality condition for subgroups of infinite augmentation dimension.